AN UNUSUAL CAUSE OF UPPER GASTROINTESTINAL BLEEDING - Ali, Kishwar; Zarin, Muhammad; Latif, Humera (Journal of Ayub Medical College Abbottabad, 2015)
Gastrointestinal haemorrhage (GI) is a serious condition that presents both diagnostic as well as therapeutic challenges. Resuscitation of the patient is the first and most important step in its management followed by measures to localize and treat the exact source and site of bleeding. These modalities are upper and lower GI endoscopies, radionuclide imaging and angiography. Surgery is the last resort to handle the situation, if the patient does not respond to resuscitative measures and the various interventional procedures fail to locate and stop the bleeding. We present a case of upper GI bleeding which presented with massive per rectal bleeding and the patient was not responding to resuscitation with multiple blood transfusions. Ultimately an exploratory laparotomy was done which revealed an extra-intestinal source of bleeding into the lumen of duodenum, presenting as upper GI bleeding.